Peluang Pelaksanaan Manajemen Kolaboratif dalam Pengembangan Kawasan Situs Kota Cina sebagai Potensi Pariwisata di Kota Medan - Biliater Situngkir; Zulkifli Lubis; Abdul Kadir (Universitas Medan Area, 2020)
The development of the Chinese city site area as a tourism potential in the city of Medan is very important considering the city of Medan does not yet have natural tourism objects that are well managed. The type of study used in this research is descriptive with a qualitative approach where research is carried out to create a tourism development using the Collaborative Management (Co-Management) method. To obtain data and to deepen the implementation of collaborative management, in-depth interviews were conducted with key informants and questionnaires so that the data needed in this study was complete. Data obtained in the field, both secondary data and primary data will be compiled, presented and analyzed with a qualitative approach in the form of exposure which will then be analyzed in accordance with the research problem undertaken. The results of research conducted show that the community has been involved in the development of tourism in the Chinese city site area. But the community is still walking alone in the development of tourism. With the concept of collaborative management, it will certainly be in developing tourism that is more focused and more targeted as desired. From this research it can be concluded that the area of the Chinese city site has a huge opportunity to be developed into the tourism sector that can provide benefits for both the government, the community and the parties involved in developing tourism.